Relationship of Testic Volume Towards Semen Analysis in Male Patients in Andrology Poly, RSUD Dr. Soetomo Surabaya - Ilham Masdar Apriansyah (Universitas Airlangga, 2022)
Examination of semen / ejaculates / sperm is the first screening examination that a subfertile / infertile couple needs to undertake in an attempt to find out the cause of infertility that may come from his side. Besides spermanalysis, it is also necessary to do physical examination, especially about internal and external genital tool because as it is known abnormal result of sperm analysis can be caused by anatomical abnormalities and or testis function. To determine the relationship of testicular volume to semen analysis on male patients in Andrology clinic RSUD Dr. Soetomo Surabaya. The research is a kind of observational analytic research to find out the correlation of testicular volume to semen analysis on male patients in Andrology clinic RSUD Dr. Soetomo Surabaya by using secondary data. Based on the results of statistical tests of 64 samples by using chi square test can be seen that the value of significance or p-value 0.005 <0.05. So it can be concluded that there is a relationship between testicular volume with morphology, motility and sperm concentration. Data were analyzed using chi square test to determine the relationship between testicular volume and semen analysis. Testicular volume is one of the risk factors of decreased semen analysis results